Improving the Writing Paragraph Skills with Peer Teaching Method - Masroya Budi Sri Mulyati (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The peer teaching method is an exercise technique in learning in which students or participants present their ideas or opinions to other fellow participants. With this peer-to-peer method, it is expected that students' ability to write paragraphs will increase and be more directed based on the method given by the teacher. Therefore, this study aims to find out how to improve the ability to write paragraphs using the peer teaching method in senior high school. The research method used in this research is peer-to-peer method which is directed to describe the variable or ability to write paragraphs in senior high school students class X SMA Negeri 35 Jakarta with classroom action research (PTK). Based on the results of data analysis by looking at the results of the teaching-learning process, there was an increase in the ability to write paragraphs for aspects of unity, integration, development, as well as spelling and punctuation carried out by teachers from cycle I (78.31%) to cycle II (87.27%) with average of 13.46%. In addition, the evaluation obtained from each cycle also experienced increase of 35.13% in cycle II from Cycle I.Keywords: Pharagraps Writing skills; Peer Teaching Method; Classroom Action Research